Advances in management accounting. Vol. 21 - Epstein, Marc J.; Lee, John Y. (Advances in management accounting,, 2012)
Volume 21 includes articles on: impact of framed information and project importance on capital budgeting decisions; understanding situational participation, intrinsic involvement, and influence; the impact of adverse selection and risk propensity on managers' project evaluation decisions; relative hedonic utility and budgetary conflict resolution; management control systems, environmental uncertainty, and organizational slack; industrial relations, budgetary participation and budget use; corporate strategy, employees' attitudes towards the balances scorecard, and corporate performance using a contingency approach; the effects of information technology integration on manufacturing financial performance from the cost control system perspective; and characteristics of no-budget firms in terms of strategy, environment, planning, firm performance evaluations and management incentive rewards.